ACCELERATION OF FINANCIAL TECHNOLOGY GROWTH IN ISLAMIC BANKS AS AN EXISTENCE EFFORT TO FACE THE PANDEMIC OF COVID-19 - M IQBAL; RINOL SUMANTRI; RATIH KHOIRUNNISA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2022)
Financial Technology or what is familiarly called fintech is a platform that combines technology and finance into a technology-based financial business that makes it easier for customers so that there is no need for face-to-face transactions. Financial technology is currently trending in Indonesia, especially after the peak of the COVID-19 pandemic that occurred throughout 2020-2021, not only in banking but has begun to spread stand-alone financial technology in terms of payments and peer to peer landing. All technology-based financial institutions compete with each other, Islamic banking institutions in Indonesia, marked by the merger of three Islamic banks into one big force, namely Bank Syariah Indonesia which has optimized digital-based products to maximize the profitability of their companies. The purpose of this study is to find out the tips of Islamic Banking, especially Indonesian Islamic Banks in maximizing the profitability of their companies with fintech.